PENGARUH PENGALAMAN KERJA, KOMPETENSI, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT PADA INSPEKTORAT KOTA GORONTALO - Limonu, Abdul Aziz; Kalangi, Lintje; Afandi, Dhullo (Universitas Sam Ratulangi, 2021)
This study aims to determine the effect of: (1) Work Experience on Audit Quality at the Gorontalo City Inspectorate, (2) Competence on Audit Quality at the Gorontalo City Inspectorate, (3) Independence on Audit Quality at the Gorontalo City Inspectorate, (4) Work Experience , Competence, and Independence on Audit Quality simultaneously. This research was conducted at the Gorontalo City Inspectorate. The population used in this study is internal auditors at the Gorontalo City Inspectorate, with the sampling technique using the census method. Data collection techniques were carried out using a questionnaire. Test the quality of the data using validity and reliability tests. Classical assumption test using normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique used multiple linear regression analysis. The results showed that work experience partially had a significant positive effect on audit quality, competence partially had a significant positive effect on audit quality, and independence partially had a significant positive effect audit quality. Work experience, competence, and independence simultaneously have a positive and significant effect on audit quality.